Comprehensive Review of Mental Health Integration, Community Health Services, And Technological Innovations for Vulnerable Populations - Alsleem, Hadi Saeed Saleh; Al Jufaysh, Jufaysh Saleh Ghanem; Al Yami, Abdullah Shadad Saleh; Alqufayli, Moslah Hadi Moslah; Alyami, Mohammed Mahdi; Alyami, Saleh Mohammed Mubarak; Alyami, Wafi Mohammed Mubarak; Althaiban, Saleh Hudayban Ali; Althaiban, Ali Hudayban Ali (Journal of Ecohumanism, 2024)
Incorporating mental into community health services, in addition to technology, has become core to meeting the health needs of the vulnerable populace. This review aims to evaluate the impact of such integration on the increase of access, equity, and quality of care. It reveals how community interventions backed by technologies such as telemedicine, Mobile Health applications, and Artificial Intelligence are shaping the care of such populations. Sample findings, therefore, reveal enhanced positive mental health outcomes, service utilization, and integration into the community. Other issues include technology learning and the availability of resources, while Delaney acknowledges the applicability of the recommendations for relevant policy changes for future research.